2021
DOI: 10.7566/jpsj.90.073705
|View full text |Cite
|
Sign up to set email alerts
|

Field-Direction Sensitive Skyrmion Crystals in Cubic Chiral Systems: Implication to 4f-Electron Compound EuPtSi

Abstract: We investigate the instability toward a skyrmion crystal (SkX) in noncentrosymmetric cubic magnets with an emphasis on a comparison between point groups (O, T ) and T d . By constructing low-temperature magnetic phase diagrams under an external magnetic field for three directions based on numerically simulated annealing, we find that the system under the point group (O, T ) exhibits different two types of SkXs depending on the field direction, while that under T d does not show such an instability. The differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 79 publications
(61 reference statements)
0
32
0
Order By: Relevance
“…In addition, the model can be extended to include higher-order contributions. For instance, the four-spin biquadratic interactions ∝ (S Qη •S −Qη ) 2 [49,50,58,63,[72][73][74][75][76][77][78][79] and the six-spin bicubic interactions ∝ {S Q1 • (S Q2 × S Q3 )} 2 [61] have also been considered as the origin of stabilization of multiple-Q magnetic orderings.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the model can be extended to include higher-order contributions. For instance, the four-spin biquadratic interactions ∝ (S Qη •S −Qη ) 2 [49,50,58,63,[72][73][74][75][76][77][78][79] and the six-spin bicubic interactions ∝ {S Q1 • (S Q2 × S Q3 )} 2 [61] have also been considered as the origin of stabilization of multiple-Q magnetic orderings.…”
Section: Modelmentioning
confidence: 99%
“…In this case, J Qη in the two-spin interaction part does not have to be positive definite. Furthermore, Method II can deal with the generic form of the Hamiltonian expressed by a function of S α Qη , including multiple-spin interactions, such as the biquadratic ones 50,58,63,[72][73][74][75][76][77][78][79] and the bicubic ones…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a series of additional compounds with the B20 structure have also been identified to host magnetic skyrmions, such as Fe 1−x Co x Si [7,8], FeGe [9,10], and Cu 2 OSeO 3 [11,12]. Recently EuPtSi, which also crystallizes in a chiral cubic structure (LaIrSi-type, space group P2 1 3) [13], was shown to be an unusual example of an f -electron system hosting magnetic skyrmions [14][15][16], where the size of a single skyrmion for H [111] is only 18 Å, 10 times smaller than those in MnSi [17]. In addition to these compounds with chiral structures, it was found that compounds with a noncentrosymmetric polar structure are also promising candidates for realizing skyrmions, such as GaV 4 S 8 with a lacunar spinel structure [18], which hosts a Néel-type skyrmion phase.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, antiskyrmions have been observed in bulk materials [15][16][17] but not in thin films. While the early theoretical understanding of these textures was largely based on phenomenological magnetic models, recent years have witnessed efforts towards a microscopic electronic description of these topological textures [18][19][20][21][22][23]. Most of these recent studies focus on identifying the correct electronic model to stabilize one specific type of magnetic textures, such as, Neel-or Bloch-skyrmions or antiskyrmions.…”
mentioning
confidence: 99%